Training in developing higher-order thinking based online test instrument for biology teachers in Sekayu City - Anwar, Yenny; Selamet, Adeng; Huzaifah, Siti; Madang, Kodri (Journal of Community Service and Empowerment, 2020)
In this 21st century, teachers are required to empower students' Higher-Order Thinking Skills (HOTS). Unfortunately, there are still many teachers who have difficulty compiling HOTS questions. The purpose of this community service activity was training in formulating HOTS-based online test instrument for Senior High School (SHS) teachers in Sekayu City. Community service activities were carried out by a team from the Biology Education Study Program, Sriwijaya University through workshops. The workshop was held at Public SHS 2 Sekayu for two days. From the service activities that have been carried out, there has been an increase in the knowledge and skills of teachers in designing and making HOTS-based online evaluation tools. This activity also produced a HOTS question collection document and a google form link containing an online based HOTS question instrument. Based on the series of service activities, it can be concluded that the competence of teachers to conduct online-based HOTS evaluation activities has increased.